If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 135 = 9(f + -897) Reorder the terms: 135 = 9(-897 + f) 135 = (-897 * 9 + f * 9) 135 = (-8073 + 9f) Solving 135 = -8073 + 9f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-9f' to each side of the equation. 135 + -9f = -8073 + 9f + -9f Combine like terms: 9f + -9f = 0 135 + -9f = -8073 + 0 135 + -9f = -8073 Add '-135' to each side of the equation. 135 + -135 + -9f = -8073 + -135 Combine like terms: 135 + -135 = 0 0 + -9f = -8073 + -135 -9f = -8073 + -135 Combine like terms: -8073 + -135 = -8208 -9f = -8208 Divide each side by '-9'. f = 912 Simplifying f = 912
| (2w-2)(w)=65 | | 4(v-4)-6v= | | 23(m+27)=644 | | yi+y^2sinx=0 | | X(1)+y(2)=34 | | 7=43-k | | 160-2= | | y(y+13)=0 | | -54x-6+-37x+2=360 | | 5=(4x-8y) | | 5=4x-8y | | 5y-3+y+39=7y+40-5y | | 2a-14+a+23=b | | y^4-36y^2+1.024=0 | | 5(4x-8y)= | | 5+(n+4)=14 | | x*8=18 | | 9+5y-6=8y+6-2y | | 3(b+2)+b=3(b-2)-2 | | C/10-100=200 | | -3(-t+8-3)=-12 | | 2a-14=b | | 2q+54=-346 | | -7x+2=-14.8 | | 9=2u+1 | | -3(10-s+1)=-21 | | y-14.65/-1=-2.78 | | 3(x+4)+7=12 | | -(s+6)=18 | | (x-3)(x+4)-(5x-1)(x+7)= | | 3+(2+n)=9 | | 3p-28=p |